วาทกรรมการเมืองที่ปรากฏบนปกนิตยสารมติชนสุดสัปดาห์ - ศจีรัตน์ พุฒเรืองศักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This research was the qualitative one with the objective to study into the sign structure as appearing on the cover of the Matichon Weekly Magazine, the persons as appearing on the cover of the Matichon Weekly Magazine, pictures representing these persons, series of political discourse as appearing on the cover of the Matichon Weekly Magazine, ideal conveyance of meaning, and power of persons as appearing on the cover of the Matichon Weekly Magazine, as well as the analysis of structure of political discourse as appearing on the cover of the Matichon Weekly Magazine by studying from the cover of the Matichon Weekly Magazine of 2005 with dimensions for 38 volumes by using concept on discourse, analysis of critical discourse, concept on semiology, concept on representing pictures, and concept on creating meaning in mass media as guideline in analyzing. It was found from the study that the sign structure consisting of 1. Picture as appearing on the cover of the Matichon Weekly Magazine mostly was the presentation of pictures of persons and the denotative meaning; most of the headings of cover and messages above as appearing on the cover of the Matichon Weekly Magazine conveyed connotative meaning by presenting in a wide variety of forms and by various signs; this made it necessary for reader to interpret under the context of incidents occurring at that time. Persons as appearing on the cover of the Matichon Weekly Magazine were politicians, academicians, mass media workers, and celebrities whose pictures were created as representations as follows: 1. Main power group with underlying interest 2. Group opposing main power group 3. Group creating balance/ neutrality; these persons were presented through meaning opposing the Thaksin Government, meaning for fighting back among people, and personal meaning that reflected the ideal meaning and power as appearing on the cover of the Matichon Weekly Magazine in that the producer team of the Matichon Weekly Magazine have ideology of opposing the Thaksin Government by using the area on the cover of the Matichon Weekly Magazine in opposing main power group from creating meaning that opposed the Thaksin Government from politicians of opposition parties, academicians, and mass media workers.